The nature of symptoms: fluctuation or responsibility and freedom internally of choice - Kalishchuk, Svitlana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
The paper raises the issue of exacerbation of psychological problems caused by the political and economic environment, which creates a general social tension and becomes a background that exacerbates the existential problems of the individual. That's why author emphasizes on a particular need for the development of therapeutic direction and a detailed and well-grounded development of therapeutic concepts. It creates ways of an effective solve of current problems of psychological health and well-being of the person.The article explained the conceptual provisions of the establishment, operation and therapeutic work with the symptom. The main characteristics, structure and overall symptom phenomenological expanse from the standpoint of the existential approach of the theory of system solutions and system modeling. Psychological functions of a symptom are considered. Issues of operationalization of a symptom and definition of conceptual provisions of its formation are solved . Basic rules of interpretation of a symptom and interpretation of the concept are described in terms of several approaches. The conceptual provisions of symptom formation that allow to include it in psycho-corrective methods are considered in detail.The methods of the existential-systemic technological approach for providing psychological assistance to the client are analyzed and empirically tested, providing dynamic changes in the content of the "picture of the world" of clients in the cognitive and ontological plans. According to the empirical study, psychosomatic, emotional and behavioral symptoms were presented. It has been shown that symptoms with different specificities have unchanging constituents and functions. It also has been shown that applying an existential approach helps the symptomatic client to produce a new, better reality that will take into account the actual needs and aspirations of the subject. Thus, the main task, which is directed and work with the symptom – is the person's approach to himself/herself, greater sensitivity to his own real existential aspirations.
Keywords: symptom; freedom; responsibility; meaning; system; attractor